The effects of cognitive reappraisal following retrieval-procedures designed to destabilize alcohol memories in high-risk drinkers - Hon, Tiffany (Psychopharmacology (Berl), 2015)
RATIONALE: Addiction is a disorder of motivational learning and memory. Maladaptive motivational memories linking drug-associated stimuli to drug seeking are formed over hundreds of reinforcement trials and accompanied by aberrant neuroadaptation in the mesocorticolimbic reward system. Such memories are resistant to extinction. However, the discovery of retrieval-dependent memory plasticity has opened up the possibility of permanent modification of established (long-term) memories during ‘reconsolidation’. OBJECTIVES: Here, we investigate whether reappraisal of maladaptive alcohol cognitions performed after procedures designed to destabilize alcohol memory networks affected subsequent alcohol memory, craving, drinking and attentional bias. METHODS: Forty-seven at-risk drinkers attended two sessions. On the first lab session, participants underwent one of two prediction error-generating procedures in which outcome expectancies were violated while retrieving alcohol memories (omission and value prediction error groups). Participants in a control group retrieved non-alcohol memories. Participants then reappraised personally relevant maladaptive alcohol memories and completed measures of reappraisal recall, alcohol verbal fluency and craving. Seven days later, they repeated these measures along with attentional bias assessment. RESULTS: Omission prediction error (being unexpectedly prevented from drinking beer), but not a value prediction error (drinking unexpectedly bitter-tasting beer) or control procedure (drinking unexpectedly bitter orange juice), was associated with significant reductions in verbal fluency for positive alcohol-related words. No other statistically robust outcomes were detected. CONCLUSIONS: This study provides partial preliminary support for the idea that a common psychotherapeutic strategy used in the context of putative memory retrieval-destabilization can alter accessibility of alcohol semantic networks. Further research delineating the necessary and sufficient requirements for producing alterations in alcohol memory performance based on memory destabilization is still required.